The stable carbon isotope signature of methane produced by saprotrophic fungi - Schroll, Moritz; Keppler, Frank; Greule, Markus; Eckhardt, Christian; Zorn, Holger; Lenhart, Katharina (Biogeosciences discussions, 2020)
Abstract. Methane (CH4) is the most abundant organic compound in the atmosphere with emissions from many biotic and abiotic sources. Recent studies have shown that CH4 production occurs under aerobic conditions in eukaryotes such as plants, animals, algae and saprotrophic fungi. Saprotrophic fungi play an important role in nutrient recycling in terrestrial ecosystems by their ability to decompose plant litter. Even though the CH4 production by saprotrophic fungi has been reported, so far, no data for stable carbon isotope values of the emitted CH4 (δ13C-CH4 values) is available. In this study we measured the δ13C values of CH4 and carbon dioxide (δ13C-CO2 values) emitted by the two saprotrophic fungi Pleurotus sapidus and Laetiporus sulphureus cultivated on three different substrates pine wood, grass and corn, reflecting both C3 and C4 plants with distinguished bulk δ13C values. Applying keeling plots, we found that the δ13C source values of CH4 emitted from fungi cover a wide range from −40 mUr to −69 mUr depending on the growth substrate and fungal species. Whilst little apparent carbon isotopic fractionation (in the range of −0.3 mUr to 4.6 mUr) was calculated for δ13C values of CO2 released from P. sapidus and L. sulphureus relative to the bulk δ13C values of the growth substrates, much larger carbon isotopic fractionations (ranging from −22 mUr to −42 mUr) were observed for the formation of CH4. Whilst the two fungal species showed similar δ13CH4 source values when grown on pine wood, δ13CH4 source values differed substantially between the two fungal species when grown on grass or corn. We found that δ13CH4 source values emitted by saprotrophic fungi are highly dependent on the fungal species and the metabolized substrate. They cover a broad range of δ13CH4 values and overlap with values reported for methanogenic archaea, thermogenic degradation of organic matter and other eukaryotes.
Gesehen am 29.06.2020